Proposition of waste glass containers usage as secondary raw material for clay blocks production - Mirosavljević Zorica; Štrbac Dragana; Ubavin Dejan; Malešev Mirjana; Stanisavljević Nemanja; Štrbac Goran (Reciklaža i Održivi Razvoj, 2023)
The main objective of the present study was to propose the feasible usage of secondary raw material obtained from waste glass containers in the manufacture of clay blocks, driven by environmental benefits. Main goals were to reach a high content of waste glass in clay blocks, to use very low firing temperature and still obtain products with suitable physical and mechanical properties. Blocks with 10 wt. %, 20 wt. %, and 30 wt. % of waste glass in content were experimentally produced with the firing temperature of 880 °C. Relevant physical and mechanical properties were measured and their dependence on waste glass content was determined. Material flow analysis (MFA) showed that utilization of waste glass in clay block production can generate positive environmental impacts including landfill lifespan extension and contribution to the waste glass recycling.